Prediction of Overall Survival Rate in Patients With Hepatocellular Carcinoma Using an Integrated Model Based on Autophagy Gene Marker - Wang, Shuaiqun; Yang, Dalu; Kong, Wei (Frontiers in Genetics, 2021)
Autophagy cell which can inhibit the formation of tumor in the early stage and can promote the development of tumor in the late stage, plays an important role in the development of tumor. Therefore, it has potential significance to explore the influence of autophagy related genes on the prognosis of hepatocellular carcinoma (HCC). The differentially expressed autophagy related genes (AAGs) are selected from HCC gene expression profile data and clinical data downloaded from TCGA database, and human autophagy database (HADB). The role of AAGs in HCC is elucidated by GO functional annotation and KEGG pathway enrichment analysis. Combining with clinical data, autophagy genes related to prognosis are selected to construct the prognosis model of autophagy genes and survival curve of Kaplan Meier (KM) is drawn to estimate patients' survival between high and low risk groups. Through ROC curve drawn by univariate and multivariate Cox regression analysis, we found that seven genes with high expression level including HSP90AB1、SQSTM1、RHEB、HDAC1、ATIC、HSPB8 and BIRC5 are associated with poor prognosis of HCC patients. Then ICGC database is used to verify the reliability and robustness of the model. Therefore, the prognosis model of HCC constructed by autophagy gene can effectively predict the overall survival rate and help to find the best personalized targeted therapy of patients with HCC which can provide better prognosis for patients.